Clinical Features and Treatment Outcomes of Warm Autoimmune Hemolytic Anemia: A Retrospective Analysis of 60 Turkish Patients - (:unkn) unknown (SPRINGER INDIA, 2019)
We aimed to analyze 10-year experience of WAIHA patients at a single referral center in Turkey. Clinical data, survival outcome of sixty patients who were diagnosed with WAIHA were retrospectively analyzed. All the patients were direct antiglobulin test (DAT) positive. In 21 (30%) patients, IgG plus C3d DAT positivity was documented. 16 patients were secondary WAIHA and most common underlying causes were lymphoproliferative diseases (5 patients) and connective tissue disease (8 patients). Corticosteroids were first choice as a first line therapy with 54.5% CR and 40.2% PR rates. 43.3% of the patients relapsed after a median 12 months. In relapsed patients, rituximab and splenectomy achieved 85% overall response rates. The median OS was not reached. The median DFS was 40 months (95% CI, 19.6-60.4). OS and DFS at 36 months were 89.6% and 51.1%, respectively. DFS at 36 months was lower in patients with IgG plus C3d positive DAT than patients with only positive Ig G DAT (36 vs. 54%) but this difference could not reach statistical significance (p=0.23). WAIHA was a rare disease with a good prognosis. Corticosteroids were the first option and splenectomy and rituximab received good responses in relapsed patients. Attention should be paid especially in patients with IgG plus C3d DAT positivity since lower DFS were reported. Characteristics and pathogenesis of patients with IgG plus C3d DAT positivity was still an obscure.
Keywords: Warm autoimmune hemolytic anemia; Treatment; Mixed positive direct antiglobulin test; RITUXIMAB; ADULTS; EXPERIENCE; EFFICACY; SAFETY